2021
DOI: 10.24191/apmaj.v16i2-04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adoption of The XBRL on the Development of Stock Markets

Abstract: The paper examines the impact of adoption of the eXtensible Business Reporting Language (XBRL) on the development of stock markets using a large international sample. Our analysis was based on panel estimation techniques for 18 countries for a period of 20 years from 2000 to 2019. Our analysis provided empirical evidence that the adoption of the XBRL has a negative impact on the development of stock markets. This implies that strict policies are needed for the successful adoption of the XBRL and also a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, XBRL helps to automatically extract or exchange a part of the financial data (Sassi et al, 2021;Cahan et al, 2022). Therefore, it is expected to facilitate the creation, exchange, and comparison of information, which in turn improves the quality of financial reporting (Yang et al 2018).…”
Section: Xbrl (Extensible Business Reporting Language) and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, XBRL helps to automatically extract or exchange a part of the financial data (Sassi et al, 2021;Cahan et al, 2022). Therefore, it is expected to facilitate the creation, exchange, and comparison of information, which in turn improves the quality of financial reporting (Yang et al 2018).…”
Section: Xbrl (Extensible Business Reporting Language) and Taxonomymentioning
confidence: 99%
“…Some examined the role of XBRL adoption in the development of stock markets (Faboyede, Mukoro, Lyoha, & Odafen, 2017;Suriakumari, 2018;Sassi, Ben Othman, & Hussainey, 2021). For example, Faboyede, Mukoro, Lyoha, and Odafen (2017) found that the environmental factors, as well as operational, regulatory and technical challenges influence the application of XBRL on the Nigerian Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 99%